2003
DOI: 10.1002/ptr.1140
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic activity of lupeol from Bombax ceiba

Abstract: In the search for antiangiogenic agents from medicinal plants used in Vietnam, a methanol extract of the stem barks of Bombax ceiba was found to exhibit a significant antiangiogenic activity on in vitro tube formation of human umbilical venous endothelial cells (HUVEC). Bioactivity-guided fractionation and isolation carried out on this extract afforded lupeol as an active principle. At 50 and 30 microg/mL lupeol showed a marked inhibitory activity on HUVEC tube formation while it did not affect the growth of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 17 publications
3
73
0
Order By: Relevance
“…Compound 5, which was identified as lupane-type triterpenoid, was the most potent agent against the panel of three cell lines tested and rewardingly the compound exhibited selectivity Bagalkotkar et al 187 towards MCF-7 cells (IC 50 17.1 µM). Search of the literature revealed that lupane-type triterpenoids such as lupeol possess in vitro antitumour, antiangiogenic and apoptosis inducing properties in cancer cells (Moriarty et al, 1998;You et al, 2003;Aratanechemuge et al, 2004) which is in accordance with our findings. Interestingly, betulinic acid, another lupane-type triterpenoid with good in vitro anticancer activity was reported to be less cytotoxic to normal cells such as normal human astrocytes and melanocytes (Cichewicz and Kouzi, 2004) Basing on the above evidences, we propose that compound 5 would be less toxic against normal tissues.…”
Section: Resultssupporting
confidence: 91%
“…Compound 5, which was identified as lupane-type triterpenoid, was the most potent agent against the panel of three cell lines tested and rewardingly the compound exhibited selectivity Bagalkotkar et al 187 towards MCF-7 cells (IC 50 17.1 µM). Search of the literature revealed that lupane-type triterpenoids such as lupeol possess in vitro antitumour, antiangiogenic and apoptosis inducing properties in cancer cells (Moriarty et al, 1998;You et al, 2003;Aratanechemuge et al, 2004) which is in accordance with our findings. Interestingly, betulinic acid, another lupane-type triterpenoid with good in vitro anticancer activity was reported to be less cytotoxic to normal cells such as normal human astrocytes and melanocytes (Cichewicz and Kouzi, 2004) Basing on the above evidences, we propose that compound 5 would be less toxic against normal tissues.…”
Section: Resultssupporting
confidence: 91%
“…Recently, it was shown that compound 1 exhibits an anti-angiogenic effect through the inhibition of HUVEC tube formation (You et al 2003). In this study, we demonstrated the anti-migration activity of compound 1 against melanoma and neuroblastoma cells.…”
Section: Melanoma Cell Motilitysupporting
confidence: 52%
“…With the discovery of the role of angiogenesis in tumor growth and progression, considerable efforts have been directed towards antiangiogenic therapy as a new modality to treat human cancers. In recent years, attention has been given to identifying non-toxic, endothelial cell specific, diet-derived compounds as antiangiogenic agents for cancer therapy, in an effort to reduce the toxic side effects [3][4][5][6].…”
mentioning
confidence: 99%